Birthright Citizenship and Youth Crime - Leander Andres; Stefan Bauernschuster; Gordon B. Dahl; Helmut Rainer; Simone Schüller (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper studies the impact of birthright citizenship on youth crime. We leverage a reform which automatically granted birthright citizenship to eligible immigrant children born in Germany after January 1, 2000 and administrative crime data from three federal states. Immigrant youth who acquired citizenship at birth are substantially less likely to engage in criminal activity, with estimates indicating a 70% reduction. These results are particularly relevant in light of ongoing debates in the U.S. about abolishing birthright citizenship. Our findings suggest that inclusive citizenship policies can reduce crime and its associated costs, which in turn could strengthen social cohesion.
Keywords: D04; J15; K37; 330; birthright citizenship; crime; immigration; integration